The Need for ASEAN Environmental Maritime Security Cooperations - Arfin Sudirman; Idris; Yasmin Prisella Rabbani; Mursal Maulana; Yusa Djuyandi (Universitas Medan Area, 2023)
Environmental problems are increasingly worrying in the South East Asia region. These environmental problems are found in the mainland and the marine environment, from climate change, oil spills to debris and marine pollution. ASEAN has a significant role in facilitating collaborations and dialogues between member countries to protect the marine environment. This article examines ASEAN's effort as a regional organization to protect the marine environment from environmental security's perspective in the maritime sector. This article analyzes with C. Lamont’s qualitative method along with in-depth interview with source from CSIS, ASEAN Environmental Division, and researcher. This article argues that ASEAN acknowledges the nature of ecological security poses and, therefore, intra- and inter-regional cooperation is essential. However, ASEAN has not implemented practical cooperation because the ASEAN chairmanship system still focuses on traditional issues such as politics, security, and economy rather than the marine environment. Furthermore, due to the non-intervention principle, ASEAN has not provided binding legal instruments for ASEAN member countries since no particular body can apply legal force to all ASEAN member countries.